2008
DOI: 10.1017/s1751731108002103
|View full text |Cite
|
Sign up to set email alerts
|

Rumen-protected choline and vitamin E supplementation in periparturient dairy goats: effects on milk production and folate, vitamin B12 and vitamin E status

Abstract: We investigated the effects of rumen-protected choline (RPC) and vitamin E (VITE) administration on milk production and status of folate, vitamin B 12 and vitamin E during the periparturient period of dairy goats. Forty-eight Saanen multiparous goats were selected for the 72-day experiment, being moved to a maternity pen 30 days before expected parturition and assigned to one of the four experimental groups: control (CTR), no choline or vitamin E supplementation; choline (RPC), supplemented with 4 g/day cholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 31 publications
5
35
0
2
Order By: Relevance
“…Plasma glucose levels are consistent to those observed by Pinotti et al (2008), who analyzed the plasma of multiparous periparturient Saanen goats collected before the first meal of the day, as we did. Similar values were also observed in preprandial plasma of primiparous goats of different breeds during the first week after parturition (Anwar et al, 2012).…”
Section: Plasma Metabolitessupporting
confidence: 90%
See 1 more Smart Citation
“…Plasma glucose levels are consistent to those observed by Pinotti et al (2008), who analyzed the plasma of multiparous periparturient Saanen goats collected before the first meal of the day, as we did. Similar values were also observed in preprandial plasma of primiparous goats of different breeds during the first week after parturition (Anwar et al, 2012).…”
Section: Plasma Metabolitessupporting
confidence: 90%
“…Plasma NEFA levels are consistent to those observed by Pinotti et al (2008) in multiparous periparturient Saanen goats. At parturition, plasma NEFA concentration greatly increased in multiparous goats.…”
Section: Plasma Metabolitessupporting
confidence: 85%
“…Choline supplementation increases productivity as well as metabolic health in dairy ruminants (2,29,32). Choline is often considered as a vitamin however, unlike classical vitamins, its endogenous synthesis is possible, and a choline deficiency syndrome usually goes undetected in healthy mammals.…”
Section: Cholinementioning
confidence: 99%
“…Feedstuffs for animals contain free choline and phosphatidylcholine but these compounds in plants are relatively small and also dietary choline in feed stuffs is rapidly and extensively degraded by microbial populations in the rumen and intestinal supply is not enough to meet tissue requirements (Sharma & Erdman 1989). In periparturient dairy goats, Pinotti et al (2008) suggested that greater choline availability can improve milk production. RPC is becoming available as a commercial product and has proven beneficial to animals (Overton & Waldron 2004).…”
Section: Introductionmentioning
confidence: 99%
“…RPC products have been fed to pre-parturient dairy cows to increase the supply of choline to the small intestine with the goal of increasing milk or component yields or alleviating the development of fatty liver syndrome (Piepenbrink & Overron 2003). In periparturient dairy goats, Pinotti et al (2008) suggested that greater choline availability can improve milk production. The authors found that milk yield and 4% fat-corrected milk yield were, respectively, 210 and 350 g/day higher in RPC-supplemented goats than in non-supplemented goats.…”
Section: Introductionmentioning
confidence: 99%